Double-blind, comparative study of milnacipran and paroxetine in Japanese patients with major depression [Corrigendum] - Kamijima K (Dove Medical Press, 2013)
Kamijima K, Hashimoto S, Nagayoshi E, Koyama T. Neuropsychiatric Disease and Treatment. 2013;9:555–565. On page 559, right column, line 10 from the bottom: (0.9 to 1.2) should read (−0.9 to 1.2).Read the original article